The effect of dream report collection and dream incorporation on memory consolidation during sleep - Schoch, Sarah F.; Schredl, Michael (Journal of sleep research, 2019)
Collecting dream reports typically requires waking subjects up from their sleep - a method that has been used to study the relationship between dreams and memory consolidation. However, it is unclear whether these awakenings influence sleep-associated memory consolidation processes. Furthermore, it is unclear how the incorporation of the learning task into dreams is related to memory consolidation. In this study we compared memory performance in a word-picture association learning task after a night with and without awakenings in 22 young and healthy participants. We then examined if the stimuli from the learning task are successfully incorporated into dreams, and if this incorporation is related to the task performance the next morning. We show that while the awakenings impaired both subjective and objective sleep quality, they did not affect sleep-associated memory consolidation. When dreams were collected during the night by awakenings, memories of the learning task were successfully incorporated into dreams. When dreams were collected in the morning, no incorporations were detected. Task incorporation into non-rapid eye movement sleep dreams, but not rapid eye movement sleep dreams positively predicted memory performance the next morning. We conclude that the method of awakenings to collect dream reports is suitable and necessary for dream and memory studies. Furthermore, our study suggests that dreams in non-rapid eye movement rather than rapid eye movement sleep might be related to processes of memory consolidation during sleep.
Gesehen am 09.04.2019
First published: 08 August 2018